Правова характеристика суб’єктів громадського контролю у сфері охорони здоров’я - Крут, К. О.; Krut, K. O.; Krut Katherina (Право та інновації. - 2023. - № 4 (44). - С. 55-62, 2023)
Наукова стаття присвячена науково-теоретичному аналізу суб’єктів громадського контролю у сфері охорони здоров’я. Автором статті було проаналізовано погляди вчених, які присвячували свої роботи суб’єктам громадського контролю, та виведено своє визначення, під яким суб’єктами громадського контролю у сфері охорони здоров’я слід розуміти фізичних чи юридичних осіб, які відповідно до норм чинного законодавства України наділені певною сукупністю прав та обов’язків щодо здійснення контролю у зазначеній сфері та можуть бути учасником відповідних правовідносин. Окрім цього, було надано характеристику кожному суб’єкту громадського контролю у сфері охорони здоров’я, а саме: повноваження громадян, суб’єктам організованної громадськості (Громадські ради), політичні партії, засобам масової інформації, профспілка та органам самоорганізації населення. Кожен розглянутий суб’єкт громадського контролю у сфері охорони здоров’я відіграє власну, особливу роль у забезпеченні ефективного функціонування сфери охорони здоров’я України, що знаходить своє відображення у повноваженнях, якими вони наділені відповідно до норм чинного законодавства. Проте справедливим буде зазначити, що контрольна діяльність вказаних суб’єктів спрямована на досягнення єдиної мети: забезпечити ефективний захист законних прав та інтересів людини і громадянина у сфері охорони здоров’я України. Вважаємо за потрібним закріпити на законодавчому рівні у майбутньому Законі України «Про громадський контроль» повноваження та правовий статус суб’єктів громадського контролю у сфері охорони здоров’я, для того, щоб вони здійснювали свою діяльність на правових засадах та результати їх діяльності відігравали суттєву роль у суспільстві. Адже постає актуальне питання про реальну практичну цінність такого контролю, якщо його результати не несуть суттєвих наслідків для тих, по відношенню до кого він реалізується.

Problem setting. The issue of powers of subjects of public control in the field of health care is insufficiently developed in the scientific literature. Therefore, in the conditions of growing importance of public control in all spheres of public life, including in the field of health care, this issue becomes especially relevant. After all, the quality of such control in the field that is investigated in this scientific work directly depends on the effectiveness of the activities of these subjects. The scientific article is devoted to the scientific and theoretical analysis of subjects of public control in the field of health care. Analysis of recent researches and publications. Regarding the scientific approach to the definition of subjects of public control, it should be noted such scientists as O.O. Borbunyuk, A.S. Krupnyk, O.I. Nevmerzhynskyi, S.A. Kosinov, who made a significant scientific contribution. They included individual citizens and their associations (organized and unorganized), public councils/colleges, political parties, trade unions, public organizations, etc. as subjects of public control. We separate these approaches and take them into account in the further research of scientific work. Purpose of the research is to study and analyze different approaches and legislation regarding the definition of a subject of public control, and to provide a legal characterization of all types of subjects of public control in order to prove how important a role they play in achieving a single goal: to ensure the effective protection of legal rights and human and citizen interests in the sphere of health care of Ukraine. Article’s main body. The author of the article analyzed the views of scientists who devoted their works to the subjects of public control and derived his own definition, according to which the subjects of public control in the field of health care should be understood as natural or legal persons who, in accordance with the norms of current legislation of Ukraine are endowed with a certain set of rights and obligations regarding the exercise of control in the specified sphere and may be participants in the relevant legal relations. In addition, each subject of public control in the field of health care is characterized, namely: powers of citizens, subjects of organized public (Public Councils), political parties, mass media, trade unions and self-organization bodies of the population. Each considered subject of public control in the field of health care plays its own, special role in ensuring the effective functioning of the health care industry of Ukraine, which is reflected in the powers granted to them in accordance with the norms of current legislation. However, it would be fair to note that the control activities of these entities are aimed at achieving a single goal: ensuring effective protection of the legal rights and interests of people and citizens in the field of health care of Ukraine. We consider it necessary to note that the powers of subjects of public control in the field of health care are not directly enshrined in any normative legal act, which negatively affects its quality and effectiveness. In addition, the mechanism for taking public opinion into account in the activities of health care entities needs additional legislative clarification. In the opposite case, a completely logical question arises about the real practical value of such control, if its results do not have significant consequences for those for whom it is carried out. Conclusions and prospects for the development. We consider it necessary to enshrine at the legislative level in the future Law of Ukraine «On Public Control» the powers and legal status of subjects of public control in the field of health care, so that they carry out their activities on a legal basis and the results of their activities have consequences for whom they are carried out.

Изучены и проанализированы различные подходы и законодательства по определению субъекта общественного контроля и предоставлены правовые характеристики всем видам субъектов общественного контроля для того, чтобы доказать, насколько важную роль они играют для достижения единственной цели: обеспечить эффективную защиту законных прав и интересов человека и гражданина в сфере охраны здоровья Украины.
Legal characteristics of subjects of public control in the field of health care
Keywords: суб’єкти; громадський контроль; сфера охорони здоров’я; повноваження; subjects; public control; sphere of health care; powers; субъекты; общественный контроль; сфера здравоохранения; полномочия